Experimental Study on Dynamic Characteristics of Annular Coal Mine Sandstone after Different Temperatures. (9th May 2022) - Ping, Qi; Wu, Yulin; Gao, Qi; Wang, Shuo; Shen, Kaifan; Wang, Chen; Li, Xiangyang
Abstract : The rock mass is the main carrier of underground engineering. Many rock engineering involves rock mass excavation, and the temperature of deep rock mass increases with the depth rising. The study on the dynamic mechanical properties of annular coal mine sandstone under different temperatures has important guiding significance for mine excavation and rock engineering design and construction. To research the effect of high temperatures on the physical and dynamic mechanical characteristics of annular coal mine sandstone specimens, the physical parameters of the samples after the heating temperature from 25°C to 500°C were tested, and the dynamic splitting tests under the same loading condition were conducted by using SHPB test equipment. The findings indicate that with the temperature rising, the volume of samples increases, the mass and density decrease, and the change rate of the physical parameters of the annular sample is a little greater than that of the intact sample; as the temperature goes up, the dynamic tensile strength increases first and then decreases, there is a quadratic polynomial relationship with temperature; both the dynamic strain and the average strain rate decrease first and then increase as the temperature grows, showing a quadratic polynomial relationship with temperature; the damage degree of the annular and intact samples become worse as the temperature improved, and the fragments of specimen increase obviously after 200°C.